Effect of saline irrigation and plant-based biostimulant application on fiber hemp (Cannabis sativa L.) growth and phytocannabinoid composition - Formisano, Carmen; Fiorentino, Nunzio; Di Mola, Ida; Iaccarino, Nunzia; Gargiulo, Ernesto; Chianese, Giuseppina (Frontiers in Plant Science, 2024)
Phytocannabinoids represent the hallmark of the secondary metabolism of Cannabis sativa. The content of major phytocannabinoids is closely related to genetic variation as well as abiotic elicitors such as temperature, drought, and saline stress. The present research aimed at evaluating hemp response to saline irrigation supplied as NaCl solutions with an electrical conductivity (EC) of 2.0, 4.0 and 6.0 dS m -1 (S1, S2 and S3, respectively) compared to a tap water control (S0). In addition, the potential beneficial effect of a plant-based biostimulant (a legume protein hydrolysate) in mitigating the detrimental effects of saline irrigation on crop growth and phytocannabinoid composition was investigated. Sodium chloride saline irrigation significantly reduced biomass production only with S2 and S3 treatments, in accordance with an induced nutrient imbalance as evidenced by the mineral profile of leaves. Multivariate analysis revealed that the phytocannabinoid composition, both in inflorescences and leaves, was affected by the salinity level of the irrigation water. Interestingly, higher salinity levels (S2-S3) resulted in the predominance of cannabidiol (CBD), compared to lower salinity ones (S0-S1). Plant growth and nitrogen uptake were significantly increased by the biostimulant application, with a significant mitigation of the detrimental effect of saline irrigations.